Interactions in the Air: Adding Further Depth to Interactive Tabletops - Hilliges, Otmar; Izadi, Shahram; Wilson, Andy; Hodges, Steve; Garcia-Mendoza, Armondo; Butz, Andreas (UIST '09 Proceedings of the 22nd annual ACM symposium on User interface software and technology, 2009)
Although interactive surfaces have many unique and compelling qualities, the interactions they support are by their very nature bound to the display surface. In this paper we present a technique for users to seamlessly switch between interacting on the tabletop surface to above it. Our aim is to leverage the space above the surface in combination with the regular tabletop display to allow more intuitive manipulation of digital content in three dimensions. Our goal is to design a technique that closely resembles the ways we manipulate physical objects in the real-world; conceptually, allowing virtual objects to be picked up off the tabletop surface in order to manipulate their three dimensional position or orientation. We chart the evolution of this technique, implemented on two rear projection-vision tabletops. Both use special projection screen materials to allow sensing at significant depths beyond the display. Existing and new computer vision techniques are used to sense hand gestures and postures above the tabletop, which can be used alongside more familiar multi-touch interactions. Interacting above the surface in this way opens up many interesting challenges. In particular it breaks the direct interaction metaphor that most tabletops afford. We present a novel shadow-based technique to help alleviate this issue. We discuss the strengths and limitations of our technique based on our own observations and initial user feedback, and provide various insights from comparing, and contrasting, our tabletop implementations.